Structures of vanadium(III)-ethylenediamine-N,N′-diacetato-N,N′-di-3-propionato complexes: critical role of pπ-dπ donation in determining the coordination number - Meier, Roland; Mitzenheim, Steffi; Pritzkow, Hans; Eldik, Rudi van (Inorganic chemistry, 2011)
Li[V(eddadp)]·3H2O (1a) and Cs[V(eddadp)]·2H2O (1b) were characterized by X-ray crystallography. 1a crystallizes in the monoclinic space group Cc with a = 11.467(7) Å, b = 13.398(8) Å, c = 12.529(8) Å, β = 114.85(4)°; V = 1746.7(2) Å3, and Z = 4; 1b crystallizes in the monoclinic space group P21/n with a = 10.265(5) Å, b = 11.673(6) Å, c = 15.507(8) Å, β = 104.29(2)°, V = 1800.6(2) Å3, and Z = 4. The solution structure of 1 has been ascertained to be predominantly six-coordinated with a hexadentate eddadp which is based on a comparison of the electronic and Raman spectra of aqueous solutions of 1 with those in the solid state.
Published online 29 December 2010
Im Zusatz zum Titel ist das Zeichen "π" tiefgestellt
Gesehen am 17.08.2022